2020
DOI: 10.47391/jpma.125
|View full text |Cite
|
Sign up to set email alerts
|

Management of muscle trigger points causing subacromial pain using dry needling technique — a case report

Abstract: Abstract We present a case of a 22-year-old university sportsman who presented at a private hospital in Lahore in December 2018 with complaint of severe pain in the anterolateral aspect of the right shoulder after playing cricket. On palpation, greater tubercle of the right shoulder was found to be tender along with the muscle belly of supraspinatus. A muscle trigger point was identified during palpation, while painful arc was also present on abduction. Physical tests, including Hawkins-Kennedy, Neers si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Four of the six included trials were RCTs [ 16 , 17 , 23 , 56 ]. One study reported two sessions of DNY [ 57 ], two studies three sessions of DNY [ 16 , 56 ], and lastly, three studies only one session [ 17 , 22 , 23 ]. Four studies associated DNY with other treatments (manual therapy, strengthening exercises, diacutaneous fibrolysis (DF), stretching) [ 22 , 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Four of the six included trials were RCTs [ 16 , 17 , 23 , 56 ]. One study reported two sessions of DNY [ 57 ], two studies three sessions of DNY [ 16 , 56 ], and lastly, three studies only one session [ 17 , 22 , 23 ]. Four studies associated DNY with other treatments (manual therapy, strengthening exercises, diacutaneous fibrolysis (DF), stretching) [ 22 , 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…One study reported two sessions of DNY [ 57 ], two studies three sessions of DNY [ 16 , 56 ], and lastly, three studies only one session [ 17 , 22 , 23 ]. Four studies associated DNY with other treatments (manual therapy, strengthening exercises, diacutaneous fibrolysis (DF), stretching) [ 22 , 56 , 57 ]. Nevertheless, all studies evaluated pain, and all outcomes were assessed at a short-term follow-up.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dry Needling -Over the rhomboids, infraspinatus, and supraspinatus muscles, dry needling was used to minimize discomfort and trigger points[5].Exercises-The exercise regimen comprised finger stair exercises, posture, pectoral and trapezius stretching activities, shoulder range of motion exercises, and shoulder stretching exercises. Exercises for rotator cuff and scapular muscle strengthening were undertaken once the patient had reached an active full range of motion.…”
mentioning
confidence: 99%